2021
DOI: 10.3390/jtaer16050083
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison and Interpretation of Machine Learning Algorithm for the Prediction of Online Purchase Conversion

Abstract: Machine learning technology is recently being applied to various fields. However, in the field of online consumer conversion, research is limited despite the high possibility of machine learning application due to the availability of big data. In this context, we investigate the following three research questions. First, what is the suitable machine learning model for predicting online consumer behavior? Second, what is the good data sampling method for predicting online con-sumer behavior? Third, can we inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 67 publications
0
17
1
Order By: Relevance
“…In cases where the paper showed several methods and results, the model with the best performance was chosen. The lowest response rate in the previously used datasets was 2.29% (conversion rate) [14], while the highest was 27.42% [7], which is significantly higher than the response rate in this study.…”
Section: Literature Reviewcontrasting
confidence: 80%
See 2 more Smart Citations
“…In cases where the paper showed several methods and results, the model with the best performance was chosen. The lowest response rate in the previously used datasets was 2.29% (conversion rate) [14], while the highest was 27.42% [7], which is significantly higher than the response rate in this study.…”
Section: Literature Reviewcontrasting
confidence: 80%
“…Several recent papers treat this issue regarding online direct marketing campaigns and overall online purchase prediction using web log data. For instance, Lee et al [14] explored machine learning models and potential effective data sampling methods for predicting online consumer behaviour for the visitors of a Google Merchandise Store. The authors found that the eXtreme Gradient Boosting (XGB) algorithm is most effective for predicting purchase conversion of online consumers, while oversampling with the SMOTE algorithm was shown to be the best method to solve the data imbalance issue.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of machine learning algorithms to the marketing field has raised much attention due to the availability of big data along with the complex marketing environment, which is increasingly difficult to predict [34]. Ma and Sun [35] provided a systematical overview of marketing research with machine learning methods.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the further development of artificial intelligence, we have also witnessed and been surprised at how AI has become part of our popular culture. Especially since 1997, when International Business Machine Corporation (IBM)'s Deep Blue defeated Garry Kasparov, the world chess champion, people have gained a deeper understanding of AI [6][7][8]. Nowadays, intelligent personal assistants (IPAs) have become popular and common among premiumtier smartphones.…”
Section: Introductionmentioning
confidence: 99%